Handbook of orthognathic treatment : a team approach - Ayoub, Ashraf (Hoboken : Wiley, 2013)
This handbook provides a short, contemporary text on the management of dentofacial deformities. The importance of a well organised, inter-disciplinary approach is emphasised throughout and the following key areas are presented: A detailed account of the role of the psychologist, from initial assessment through to post-operative support. A systematic approach to dentofacial assessment, including a section on diagnostic records and an overview of cephalometry. A logical step-by-step approach to treatment planning, emphasising the interactive thought process required.
4.2.2 Control of incisor decompensation4.2.3 Vertical tooth movements; 4.2.4 Transverse tooth movements; 4.2.5 Orthodontic preparation for segmental surgery; 4.2.6 Progress monitoring; 4.3 Peri-operative orthodontics; 4.3.1 Fixed appliance preparation for surgery; 4.3.2 Inter-maxillary fixation; 4.3.3 The occlusal wafer; 4.3.4 Orthodontic procedures in theatre; 4.4 Post-surgical orthodontics; 4.4.1 Post-surgical healing phase; 4.4.2 Post-surgical tooth movement; 4.4.3 Retention; 4.5 Surgery before orthodontics; 4.5.1 Advantages; 4.5.2 Disadvantages; 4.6 Surgery without orthodontics.
4.7 Complications of orthodontic treatment.
Print version record.
Keywords: Orthodontics -- Handbooks, manuals, etc; Medical; MEDICAL -- Surgery -- General; Orthodontics; Electronic books; Handbooks and manuals